Adjacent crop type impacts potential pollinator communities and their pollination services in remnants of natural vegetation. (26th April 2022) - Reynolds, Victoria A.; Cunningham, Saul A.; Rader, Romina; Mayfield, Margaret M.
Abstract: Aim: Pollination plays a crucial role in the conservation of many plant species persisting in fragmented, human‐dominated landscapes. Pollinators are known to be instrumental in maintaining genetic diversity and metapopulation dynamics for many plant species and are important for providing ecological services that are essential in agricultural landscapes where populations of native plants are highly isolated. Numerous studies have explored the value of remnant native vegetation for supporting pollination services to crop species, yet the effect of mass‐flowering crops on the pollinator communities and the pollination services they provide to native plant communities persisting in fragmented landscapes are less well understood. Here, we assess the influence of the presence and phenology of a mass‐flowering crop to pollinator community structure, abundance, and pollen load composition in remnant vegetation in complex agricultural landscapes. Location: South‐west Western Australia, Australia. Methods: We recorded the composition and abundance of insect flower visitors and their pollen loads in isolated remnants of York Gum‐Jam woodlands adjacent to canola (insect‐attracting) or wheat (non‐insect‐attracting) fields over two years. Results: All bees were much more sensitive to adjacent crop type (neighbouring canola or wheat) than non‐bee pollinators. Honeybees were the most abundant pollinators in canola fields during peak flowering. Honeybee abundance increased in canola‐adjacent reserves post canola bloom, potentially indicating a movement into reserves as crop flowering waned. Native bees were the most diverse in remnant vegetation. Pollen loads of native bees were more mixed (increased pollen richness and evenness) when sampled next to canola fields compared to wheat fields. Main conclusion: The availability of potential insect pollinators to remnant wildflower communities in agricultural landscapes is context dependent. Whether sampled communities were adjacent to wheat or canola in a landscape significantly impacted the abundance of potential pollinators in certain landscape elements, but not others, and the composition of pollen loads carried by these insects. Results offer novel insights about the influence of landscape context on pollinator communities and the potential pollination services available for the conservation of native plant species in highly fragmented agricultural landscapes.